Evaluation of Some Physico-Chemical Characteristics of Kemeriz Dam (Zara – Sivas) - Mutlu, Ekrem; Demi̇r, Tuğba (Central Fisheries Research Institute (SUMAE), 2016)
Abstract The objectives of this study were to observe the monthly and annual changes in water samples through physico-chemical methods, to determine the water quality properties, to reveal the pollution problems, to determine the suitability level in terms of aquatic life, and to classify the quality of water in accordance with the Surface Water Quality Regulation (SWQR) criteria. This study was carried out through monthly sampling during January 2011-December 2013 in 3 stations at Kemeriz Dam. The water quality in Kemeriz dam was found to be Class I according to the SWQR. In order to protect the water quality and to ensure the health of aquatic life in this dam, it is required to make regular observations and to monitor the parameters affecting the water quality and aquatic life. Keywords : Sivas, Kemeriz, water quality, Kemeriz Dam Kemeriz Baraji Golunun (Zara – Sivas) Bazi Fizikokimyasal Ozelliklerinin Degerlendirilmesi Bu calismanin amaci fiziko-kimyasal metotlarla su orneklerindeki aylik ve mevsimsel degisiklikleri gozlemlemek, su kalitesi ozelliklerini belirlemek, kirlilik sorunlarini ortaya koymak, sucul hayat icin uygunlugu ortaya cikarmak ve Yuzey Sulari Kalitesi Duzenlemesi (YSKY) kriterleri uyarinca suyun kalitesini siniflandirmaktir. Bu calisma Ocak 2011 ile Aralik 2013 arasinda aylik olarak Kemeriz Baraj Golu uzerinde 3 istasyondan alinan su ornekleri ile gerceklestirilmistir. Kemeriz Baraj Golunun su kalitesi YSKY kriterlerine gore 1. Sinif olarak bulunmustur. Su kalitesini korumak ve sucul hayatin saglikli devamliligi icin duzenli gozlemler yapmak ve su kalitesi ve sucul hayati etkileyecek parametreleri takip etmek gerekmektedir. Anahtar Kelimeler : Sivas, Kemeriz, su kalitesi, Kemeriz Baraj Golu
Keywords: Sivas; Kemeriz; su kalitesi; Kemeriz Baraj Gölü; Çevre Bilimleri; Sivas; Kemeriz; water quality; Kemeriz Dam; 13. Climate action; 14. Life underwater; 6. Clean water